Ti2AlNb-based composite material with micro / nano dual-scale structure and heat treatment method thereof
Patent Information
- Application Number
- CN202611429024.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-27
Smart Images

Figure CN122979781A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heat treatment technology for intermetallic compound materials, and particularly relates to a Ti2AlNb-based composite material with a micro / nano dual-scale microstructure and its heat treatment method. Background Technology
[0002] Ti2AlNb-based intermetallic compounds are considered important candidate structural materials for the aerospace industry in the 650–800 °C temperature range due to their low density, high specific strength, high elastic modulus, and excellent high-temperature oxidation and creep resistance. However, Ti2AlNb alloys and their composites still face challenges in practical applications, such as insufficient room-temperature plasticity and the difficulty in synergistically improving strength and plasticity, which limits their further engineering applications.
[0003] Ti₂AlNb alloys are typical multiphase intermetallic compounds, mainly composed of O, B₂, and α₂ phases. Among them, the O phase, as the main strengthening phase, has a significant impact on the material's mechanical properties due to its size, morphology, orientation, and spatial distribution. Generally, coarse O phase lamellar structures can improve the material's deformation compatibility and thus enhance its plasticity; while fine nanoscale O phases can effectively hinder dislocation movement and improve the material's strength.
[0004] Existing heat treatment processes typically focus on controlling the microstructure at a specific target scale. Heat treatment in the O+B2 two-phase region yields lamellar O / B2 microstructures to improve plasticity, while aging at lower temperatures precipitates fine O phases to enhance strength. This single-scale approach inherently contradicts itself. While coarse O phases are beneficial for deformation coordination, their low interphase density limits their ability to impede dislocation movement, thus restricting the strength increase. Although fine nano-O phases offer significant strengthening effects, they are prone to coarsening during prolonged holding times, and their precipitation behavior is difficult to actively control, often accompanied by a decrease in plasticity. Even with attempts to adjust temperature or holding time, it is difficult to simultaneously and stably retain both scales of O phases within the same matrix.
[0005] Micron-sized and nano-sized O phases exhibit significant differences in precipitation thermodynamics and growth kinetics. The phases that form first are prone to coarsening or re-dissolving at subsequent high temperatures, while the later-precipitated phases struggle to nucleate uniformly within the already coarsened matrix. Furthermore, prolonged heat treatment easily leads to β-grain growth and network structure disruption, further complicating microstructure stability control. Therefore, existing heat treatment processes struggle to effectively regulate the precipitation sequence, element diffusion paths, and growth behavior of the O phase, and cannot achieve a hierarchical distribution of micron-sized and nano-sized O phases within the same material while maintaining structural stability. The problem of balancing strength and plasticity remains fundamentally unresolved. How to achieve these microstructure control objectives through the rational design of heat treatment processes is a pressing technical challenge in this field. Summary of the Invention
[0006] To address the problem of the uniform size of the O phase and the difficulty in synergistically improving strength and plasticity in Ti2AlNb-based composites, this invention provides a Ti2AlNb-based composite material with a micro / nano dual-scale microstructure and its heat treatment method.
[0007] The technical solution of the present invention:
[0008] A heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure includes the following steps:
[0009] Step 1: Place the powder metallurgy Ti2AlNb-based composite material under vacuum or protective atmosphere conditions and perform medium-temperature solution treatment at 850~970℃. After holding at this temperature for 0.5~2.5h, cool it with water or oil.
[0010] Step 2: The solid solution sample obtained in Step 1 is subjected to low-temperature aging treatment at 650~800℃ under vacuum or protective atmosphere conditions. After holding at this temperature for 4~24h, it is air-cooled or furnace-cooled to room temperature, thereby obtaining a heterogeneous structure in which micron-scale O phase and nano-scale O phase are synergistically distributed in the matrix.
[0011] Furthermore, the powder metallurgy-state Ti2AlNb-based composite material described in step one is a network (Ti,Nb)B / Ti2AlNb-based composite material containing (Ti,Nb)B whiskers.
[0012] Furthermore, the content of (Ti,Nb)B whiskers in the network (Ti,Nb)B / Ti2AlNb-based composite material is 0.1~0.5 vol.%.
[0013] Furthermore, the powder metallurgy-state Ti2AlNb-based composite material is prepared by spark plasma sintering or hot pressing sintering.
[0014] Furthermore, after the heat preservation step one is completed, the sample transfer time by water cooling or oil cooling is less than 3 seconds.
[0015] Furthermore, in both steps one and two, the vacuum atmosphere is maintained below 1 Pa.
[0016] Furthermore, in both steps one and two, the protective atmosphere is argon atmosphere, and the argon pressure is 0.05~0.15MPa.
[0017] A Ti2AlNb-based composite material prepared by the heat treatment method provided by the present invention, wherein the matrix of the composite material contains both micron-scale O phase structure and nano-scale O phase structure.
[0018] Furthermore, the average thickness of the micron-scale O-phase structure is 0.15~0.50 μm, and the average thickness of the nano-scale O-phase structure is 10~60 nm.
[0019] The beneficial effects of this invention are:
[0020] This invention achieves comprehensive control over the evolution of the O phase size in Ti2AlNb-based composites by regulating intermediate-temperature solution treatment and low-temperature aging, avoiding the problem of insufficient O phase size control in single heat treatment processes. In the intermediate-temperature solution treatment stage, a micron-sized O phase framework is formed. The network-distributed (Ti,Nb)B whiskers within the composite material exert a grain boundary pinning effect, inhibiting β-grain boundary migration and grain coarsening. This protects the original network structure from damage by high-temperature heat treatment and provides a microstructural basis for the stable coexistence of the subsequent dual-scale O phases. In the low-temperature aging stage, nano-sized O phases precipitate between the micron-sized O phases, and the pre-formation of micron-sized O phases restricts the coarsening of the nano-sized O phases. The two stages work synergistically, enabling the micron-scale and nano-scale O phases to co-distribute within the same matrix. The micron-sized O phase improves the microstructure's ability to coordinate deformation, while the nano-sized O phase enhances strengthening capabilities. Together, they achieve a simultaneous improvement in strength and plasticity. Compared to the original composite material without staged heat treatment, the Ti2AlNb-based composite material after intermediate-temperature solution treatment and low-temperature aging staged heat treatment shows a 3.6% increase in room temperature tensile strength and a 45% increase in elongation. The present invention has a simple process, and the microstructure can be controlled simply by designing the heat treatment path. It does not require changing the material composition and has good engineering application value. Attached Figure Description
[0021] Figure 1 The image shows the microstructure of the original network (Ti,Nb)B / Ti2AlNb-based composite material prepared by powder metallurgy in Example 1.
[0022] Figure 2 This is a diagram showing the O phase thickness distribution of the original network (Ti,Nb)B / Ti2AlNb-based composite material prepared by powder metallurgy in Example 1.
[0023] Figure 3 The image shows the microstructure of the network (Ti,Nb)B / Ti2AlNb-based composite material obtained by solution treatment in Example 1.
[0024] Figure 4 The images show the microstructure of the network (Ti,Nb)B / Ti2AlNb-based composite material obtained by solution treatment and aging graded heat treatment in Example 1. A is a low-magnification morphology image, and B is a local high-magnification morphology image.
[0025] Figure 5 This is a micron-scale O-phase thickness distribution diagram of the network (Ti,Nb)B / Ti2AlNb-based composite material obtained by solution treatment and aging graded heat treatment in Example 1.
[0026] Figure 6 This is a nanoscale O phase thickness distribution diagram of the network (Ti,Nb)B / Ti2AlNb-based composite material obtained by solution treatment and aging graded heat treatment in Example 1.
[0027] Figure 7 The image shows a comparison of the engineering stress-strain curves of the original network (Ti,Nb)B / Ti2AlNb-based composite material in Example 1 and the network (Ti,Nb)B / Ti2AlNb-based composite material obtained by solution treatment and aging graded heat treatment. Detailed Implementation
[0028] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0029] Example 1
[0030] This embodiment provides a heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure.
[0031] In this embodiment, a network (Ti,Nb)B / Ti2AlNb-based composite material was prepared using conventional powder metallurgy methods. The matrix material was a Ti-22Al-25Nb-0.5Mo-0.3Si (atomic percentage) pre-alloyed powder prepared by gas atomization, with an average particle size of 100 μm. TiB2 powder was used as the boron source, added at 0.125 wt.%, meaning that TiB2 powder accounted for 0.125% of the total mass of TiB2 powder and Ti2AlNb pre-alloyed powder. The average particle size of the TiB2 powder was 3 μm.
[0032] TiB2 powder and Ti2AlNb pre-alloyed powder were mixed using a low-energy ball milling process at a speed of 150 rpm for 4 hours, with a ball-to-powder ratio of 3:1. The resulting mixture was then loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace. Before sintering, the furnace was evacuated to below 1 Pa. The sintering temperature was 1300℃, the sintering pressure was 35 MPa, and the holding time was 2 hours, after which the mixture was cooled to room temperature in the furnace.
[0033] During sintering, TiB2 and the Ti2AlNb matrix undergo an in-situ autogenous reaction, with Nb partially replacing Ti to form (Ti,Nb)B. The calculated content of (Ti,Nb)B whiskers in the resulting composite material is 0.25 vol.%. The generated (Ti,Nb)B whiskers grow near the surface of the spherical matrix alloy particles, distributed along the original powder particle boundaries, forming a three-dimensional quasi-continuous network structure.
[0034] The original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment was subjected to metallographic etching and then observed by scanning electron microscopy. The resulting microstructure image is shown below. Figure 1 As shown, the white area represents the B2 phase, and the gray lamellar structures represent the O phase. It can be seen that the O phase size is on the order of micrometers. The O phase thickness distribution was statistically obtained under a scanning electron microscope as shown in the image. Figure 2 As shown, the average thickness of the original O phase laths is 0.2 μm.
[0035] Using the original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment as a heat treatment sample, a graded heat treatment method was adopted for processing. The specific steps are as follows:
[0036] Step 1, short-time medium-temperature solution treatment:
[0037] First, the temperature of the box-type resistance furnace was raised to 950℃. Then, the original network (Ti,Nb)B / Ti2AlNb-based composite material was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The solution was held at the solution temperature of 950℃ for 1 hour. After the holding time was completed, the solution-treated sample was placed in water for water cooling within 3 seconds to preserve the microstructure at the intermediate temperature.
[0038] Step 2: Long-term low-temperature aging treatment:
[0039] First, the temperature of the box-type resistance furnace was raised to 750℃. Then, the composite material after the solution treatment in step one was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The aging temperature was maintained at 750℃ for 6 hours. After the holding time was completed, the sample was taken out of the furnace and air-cooled to room temperature to obtain a (Ti,Nb)B / Ti2AlNb-based composite material with a micro-nano dual-scale structure.
[0040] The composite material obtained by solution treatment in this embodiment was subjected to metallographic etching and then observed by scanning electron microscopy. The resulting microstructure image is shown below. Figure 3 As shown, the O-phase lamellar structure is a single micrometer-scale structure with an average O-phase lamellar thickness of 0.325 μm.
[0041] The composite material obtained by solution treatment and aging-graded heat treatment in this embodiment was subjected to metallographic etching and then observed by scanning electron microscopy. The resulting microstructure image is shown below. Figure 4As shown, the O phase size changed from a single micrometer-scale uniform distribution to a micro-nano dual-scale heterogeneous distribution, and its network structure remained intact after prolonged heat treatment. The O phase thickness distribution was statistically obtained under a scanning electron microscope as shown in the figure. Figure 5 and Figure 6 As shown, the average size of the micron-scale O phase laths is 0.388 μm, while that of the nano-scale O phase laths is only 31.5 nm. This proves that the micro-nano dual-scale heterogeneous microstructure was constructed through hierarchical heat treatment.
[0042] During powder metallurgy, (Ti,Nb)B whiskers are distributed along the boundaries of the original Ti2AlNb powder particles, i.e., the original β grain boundaries, forming a three-dimensional quasi-continuous network framework. The size of this network corresponds to the spatial distribution range of the original β grain boundaries. Therefore, changes in the network structure size can indirectly reflect whether the original β grain boundaries have significantly migrated during heat treatment. To investigate whether the original β grain boundaries have significantly migrated during graded heat treatment and to verify the grain boundary pinning effect of (Ti,Nb)B whiskers, the network structure sizes of the original composite material obtained through powder metallurgy and the composite material obtained through solution treatment followed by aging graded heat treatment were statistically analyzed. The results are shown in Table 1.
[0043] Table 1
[0044]
[0045] As shown in Table 1, the average difference in the size of the network structure of the composite material before and after the graded heat treatment is only 2.6 μm, which is within the statistical error range. This indicates that the high-temperature holding during the graded heat treatment process did not lead to a significant increase in the size of the network structure. Given that the (Ti,Nb)B whiskers are distributed in a network along the original β grain boundaries, the above results show that the whiskers effectively pinned the original β grain boundaries during the graded heat treatment process, inhibiting grain boundary migration and β grain coarsening. This directly confirms the pinning effect of the network (Ti,Nb)B whiskers on β grain growth. This pinning effect ensures the stability of the network structure during the graded heat treatment process, providing an organizational basis for the stable coexistence of micron-sized O phase and nano-sized O phase in a limited space, which is conducive to achieving a synergistic improvement in strength and plasticity.
[0046] Using the original composite material obtained by powder metallurgy, the composite material obtained by solution treatment only, and the composite material obtained by solution treatment plus aging graded heat treatment as samples, room temperature tensile tests were conducted according to GB / T 228.1 to determine the yield strength, tensile strength, and elongation after fracture. Engineering stress-strain curves were plotted, and the results are shown in Table 2. Figure 7 .
[0047] Table 2
[0048]
[0049] From Table 2 and Figure 7 It can be seen that although the elongation of the composite material obtained by solution treatment alone is improved compared with the original composite material, the tensile strength is reduced by 76.3 MPa, indicating that solution treatment alone has the limitation of sacrificing strength for plasticity. Compared with the original composite material, the composite material obtained by staged heat treatment has an increased tensile strength of 3.6% and an increased elongation of 45%, indicating that constructing a micro / nano dual-scale O phase structure can restore strength while retaining the plasticity improvement effect of solution treatment, and further achieve a synergistic improvement in the room temperature strength and plasticity of Ti2AlNb-based composite materials.
[0050] Example 2
[0051] This embodiment provides a heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure.
[0052] In this embodiment, a network (Ti,Nb)B / Ti2AlNb-based composite material was prepared using the same conventional powder metallurgy method as in Example 1. The original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment was used as a heat treatment sample, and a graded heat treatment method was employed. The specific steps are as follows:
[0053] Step 1, short-time medium-temperature solution treatment:
[0054] First, the temperature of the box-type resistance furnace was raised to 910℃. Then, the original network (Ti,Nb)B / Ti2AlNb-based composite material was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The solution was held at the solution temperature of 910℃ for 1 hour. After the holding time was completed, the solution-treated sample was placed in water for water cooling within 3 seconds to preserve the microstructure at the intermediate temperature.
[0055] Step 2: Long-term low-temperature aging treatment:
[0056] First, the temperature of the box-type resistance furnace was raised to 750℃. Then, the composite material after the solution treatment in step one was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The aging temperature was maintained at 750℃ for 6 hours. After the holding time was completed, the sample was taken out of the furnace and air-cooled to room temperature to obtain a (Ti,Nb)B / Ti2AlNb-based composite material with a micro-nano dual-scale structure.
[0057] Example 3
[0058] This embodiment provides a heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure.
[0059] In this embodiment, a network (Ti,Nb)B / Ti2AlNb-based composite material was prepared using the same conventional powder metallurgy method as in Example 1. The original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment was used as a heat treatment sample, and a graded heat treatment method was employed. The specific steps are as follows:
[0060] Step 1, short-time medium-temperature solution treatment:
[0061] First, the temperature of the box-type resistance furnace was raised to 930℃. Then, the original network (Ti,Nb)B / Ti2AlNb-based composite material was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The solution was held at the solution temperature of 930℃ for 1 hour. After the holding time was completed, the solution-treated sample was placed in water for water cooling within 3 seconds to preserve the microstructure at the intermediate temperature.
[0062] Step 2: Long-term low-temperature aging treatment:
[0063] First, the temperature of the box-type resistance furnace was raised to 750℃. Then, the composite material after the solution treatment in step one was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The aging temperature was maintained at 750℃ for 6 hours. After the holding time was completed, the sample was taken out of the furnace and air-cooled to room temperature to obtain a (Ti,Nb)B / Ti2AlNb-based composite material with a micro-nano dual-scale structure.
[0064] Example 4
[0065] This embodiment provides a heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure.
[0066] In this embodiment, a network (Ti,Nb)B / Ti2AlNb-based composite material was prepared using the same conventional powder metallurgy method as in Example 1. The original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment was used as a heat treatment sample, and a graded heat treatment method was employed. The specific steps are as follows:
[0067] Step 1, short-time medium-temperature solution treatment:
[0068] First, the temperature of the box-type resistance furnace was raised to 950℃. Then, the original network (Ti,Nb)B / Ti2AlNb-based composite material was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The solution was held at the solution temperature of 950℃ for 2 hours. After the holding time was completed, the solution-treated sample was placed in water for water cooling within 3 seconds to preserve the microstructure at the intermediate temperature.
[0069] Step 2: Long-term low-temperature aging treatment:
[0070] First, the temperature of the box-type resistance furnace was raised to 750℃. Then, the composite material after the solution treatment in step one was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The aging temperature was maintained at 750℃ for 6 hours. After the holding time was completed, the sample was taken out of the furnace and air-cooled to room temperature to obtain a (Ti,Nb)B / Ti2AlNb-based composite material with a micro-nano dual-scale structure.
[0071] Example 5
[0072] This embodiment provides a heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure.
[0073] In this embodiment, a network (Ti,Nb)B / Ti2AlNb-based composite material was prepared using the same conventional powder metallurgy method as in Example 1. The original network (Ti,Nb)B / Ti2AlNb-based composite material obtained in this embodiment was used as a heat treatment sample, and a graded heat treatment method was employed. The specific steps are as follows:
[0074] Step 1, short-time medium-temperature solution treatment:
[0075] First, the temperature of the box-type resistance furnace was raised to 970℃. Then, the original network (Ti,Nb)B / Ti2AlNb-based composite material was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The solution was held at the solution temperature of 970℃ for 1 hour. After the holding time was completed, the solution sample was placed in water for water cooling within 3 seconds to preserve the microstructure at the intermediate temperature.
[0076] Step 2: Long-term low-temperature aging treatment:
[0077] First, the temperature of the box-type resistance furnace was raised to 750℃. Then, the composite material after the solution treatment in step one was placed in the box-type resistance furnace, and the vacuum degree inside the furnace was maintained below 1 Pa. The aging temperature was maintained at 750℃ for 6 hours. After the holding time was completed, the sample was taken out of the furnace and air-cooled to room temperature to obtain a (Ti,Nb)B / Ti2AlNb-based composite material with a micro-nano dual-scale structure.
[0078] Using the solution-treated network (Ti,Nb)B / Ti2AlNb-based composite materials obtained in Examples 1-5 with different solution temperatures and holding times as samples, the thickness of the O phase laths and the O phase content after solution treatment were measured, and the results are shown in Table 3.
[0079] Table 3
[0080]
[0081] As shown in Table 3, the O-phase laths obtained during the intermediate-temperature solution treatment stage remain at the micrometer scale. However, with increasing solution temperature, the thickness of the O-phase laths gradually coarsens, increasing from 0.259 μm to 0.396 μm, while the O-phase content gradually decreases. Therefore, optimizing the solution temperature can customize the thickness of the micrometer-scale O-phase, thereby achieving precise control of the micrometer-scale O-phase.
Claims
1. A heat treatment method for Ti2AlNb-based composite materials with micro / nano dual-scale microstructure, characterized in that, Includes the following steps: Step 1: Place the powder metallurgy Ti2AlNb-based composite material under vacuum or protective atmosphere conditions and perform medium-temperature solution treatment at 850~970℃. After holding at this temperature for 0.5~2.5h, cool it with water or oil. Step 2: The solid solution sample obtained in Step 1 is subjected to low-temperature aging treatment at 650~800℃ under vacuum or protective atmosphere conditions. After holding at this temperature for 4~24h, it is air-cooled or furnace-cooled to room temperature, thereby obtaining a heterogeneous structure in which micron-scale O phase and nano-scale O phase are synergistically distributed in the matrix.
2. The heat treatment method according to claim 1, characterized in that, The powder metallurgical Ti2AlNb-based composite material described in step one is a network (Ti,Nb)B / Ti2AlNb-based composite material containing (Ti,Nb)B whiskers.
3. The heat treatment method according to claim 2, characterized in that, The content of (Ti,Nb)B whiskers in the reticulated (Ti,Nb)B / Ti2AlNb-based composite material is 0.1~0.5 vol.%.
4. The heat treatment method according to any one of claims 1-3, characterized in that, The powder metallurgical Ti2AlNb-based composite material was prepared by spark plasma sintering or hot pressing sintering.
5. The heat treatment method according to claim 4, characterized in that, After the heat preservation step one is completed, the sample transfer time by water cooling or oil cooling is less than 3 seconds.
6. The heat treatment method according to claim 5, characterized in that, In both steps one and two, the vacuum atmosphere is maintained below 1 Pa.
7. The heat treatment method according to claim 6, characterized in that, In both steps one and two, the protective atmosphere is argon, with an argon pressure of 0.05~0.15MPa.
8. A Ti2AlNb-based composite material prepared by the heat treatment method according to any one of claims 1-7, characterized in that, The matrix of the composite material contains both micron-scale O-phase and nano-scale O-phase structures.
9. The Ti2AlNb-based composite material according to claim 8, characterized in that, The average thickness of the micron-scale O-phase structure is 0.15~0.50 μm, and the average thickness of the nano-scale O-phase structure is 10~60 nm.